Firearm safety behaviours in military families with children: Mixed-methods Study with U.S. service members and spouses - Jennifer Paruk; Sarah A. Limbacher; Ashley Brooks-Russell; Julia Finn; Ian F. Eisenhauer; Jayna Moceri-Brooks; Ian H. Stanley (Journal of Military, Veteran and Family Health, 2026)
Introduction: U.S. youth in military families experience higher rates of suicide ideation than youth from civilian families, and, given that U.S. military families also report higher rates of firearm ownership, military-connected youth may face elevated risk of firearm injury. Secure firearm storage may reduce youth suicide and unintentional injury risk, yet the factors that influence military parents’ firearm-related practices around their children are not known. Methods: The authors conducted a mixed-methods study of online survey responses from 106 U.S. military service members and their partners whose home contained firearms and children. Participants provided information on military affiliation and occupation as well as firearm-related beliefs, storage practices, and behaviours. Participants also answered open-ended questions about factors that influence their firearm-related practices and the role of military culture. Results: Nearly all parents (93%) reported storing all of their firearms locked. Parents reported how military values of discipline, responsibility, and firearm safety influenced household practices and were perceived to reduce military youth’s access to firearms. These military values, along with general safety concerns, a desire to be honest and transparent, and an emphasis that firearms can be dangerous and are tools for protection and not toys, all shaped parents’ firearm-related behaviours and conversations with their children. Joint decision-making between parents regarding firearms was common. Discussion: Military and non-military factors jointly influenced parents’ firearm practices at home. Prevention efforts for military families with respect to suicide and firearm injury may find benefit in alignment with military values of discipline, responsibility, and safety.